2011
DOI: 10.1007/s11251-010-9157-y
|View full text |Cite
|
Sign up to set email alerts
|

Creativity in advertising design education: an experimental study

Abstract: Have you ever thought about why qualities whose definitions are elusive, such as those of a sunset or a half-opened rose, affect us so powerfully? According to de Saussure (Course in general linguistics, 1983), the making of meanings is closely related to the production and interpretation of signs. All types of design, including advertising design, are about meaning-making. This study examines the effectiveness of a problembased learning (PBL) approach in enhancing student designers' creative flexibility in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…Vidic (2011) revealed that when PBL was applied, engineering students were better able to solve problems. In addition, Cheung (2011) determined that the PBL approach had a significant effect on the creative flexibility of advertising design students. Yoon, Woo, Treagust and Chandrasegaran (2014) revealed that the PBL approach had an important effect on the creative thinking skills of students in a chemistry laboratory course.…”
Section: Introductionmentioning
confidence: 99%
“…Vidic (2011) revealed that when PBL was applied, engineering students were better able to solve problems. In addition, Cheung (2011) determined that the PBL approach had a significant effect on the creative flexibility of advertising design students. Yoon, Woo, Treagust and Chandrasegaran (2014) revealed that the PBL approach had an important effect on the creative thinking skills of students in a chemistry laboratory course.…”
Section: Introductionmentioning
confidence: 99%
“…Creativity has been shown to improve through divergent-thinking techniques using metaphors and semiotics (Cheung, 2011). To demystify the creative process for students, Cotzias (1996) detailed a thinking process of listing five initial benefits about a product or brand, then developing tangents to those benefits.…”
Section: Literature Review Teaching Creative Thinkingmentioning
confidence: 99%
“…Hmelo-Silver (2004) said, "Educators are interested in PBL because of its emphasis on active, transferable learning and its potential for motivating students" (p. 236). Cheung (2011) reported PBL to be a successful approach in nursing, criminal justice, engineering, management, mass communication and marketing, while Artino (2008) noted that PBL methods have been employed in K-12 schools to help teach mathematics and other subjects to young children.…”
Section: R E West G Williams and D Williamsmentioning
confidence: 99%
“…Belski (2009), for example, studied the effectiveness of teaching thinking and creative problem solving through the Theory of Inventive Problem Solving approach and found that students perceived the course to be useful, to improve their problem solving skills, and to help them become more systematic and structured in their approach to solving problems. Cheung (2011) looked specifically at how problem-based learning affected creativity in advertising design students over a traditional lecture approach and similarly found that the group participating in PBL exhibited much higher creative flexibility.…”
Section: R E West G Williams and D Williamsmentioning
confidence: 99%
See 1 more Smart Citation